2010
DOI: 10.1038/clpt.2010.149
|View full text |Cite
|
Sign up to set email alerts
|

The FDA Should Eliminate the Ambiguities in the Current BCS Biowaiver Guidance and Make Public the Drugs for Which BCS Biowaivers Have Been Granted

Abstract: Although FDA approved BCS Class 1 drugs are designated as high permeability, in fact, the criterion utilized is high extent of absorption. This ambiguity should be eliminated and the FDA criterion should explicitly be stated as ≥ 90% absorption based on absolute bioavailability or mass balance. Maintaining confidentiality of the drugs for which the FDA has approved BCS waivers of in vivo bioequivalence studies is not good public policy and should be reversed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 7 publications
1
32
0
1
Order By: Relevance
“…Yee (10) had reported that Caco-2 can accurately predict the human intestinal permeability or absorption of compounds regardless of transcellular, paracellular, and carrier-mediated transport mechanisms. However, there are Caco-2 permeability results that disagree with measured human intestinal permeability rates or measured extents of human intestinal absorption (11,12).…”
Section: Introductionmentioning
confidence: 69%
“…Yee (10) had reported that Caco-2 can accurately predict the human intestinal permeability or absorption of compounds regardless of transcellular, paracellular, and carrier-mediated transport mechanisms. However, there are Caco-2 permeability results that disagree with measured human intestinal permeability rates or measured extents of human intestinal absorption (11,12).…”
Section: Introductionmentioning
confidence: 69%
“…As noted above, BDDCS predictions and classification are based on the intestinal permeability rate, not the extent of permeability. There is some ambiguity with respect to the basis for BCS, as reviewed by Benet and Larregieu (6). The initial permeability studies of Amidon, Lennernäs, and colleagues (5,8), as summarized by Takagi et al (3), show a good correlation between human intestinal permeability rate and the extent of absorption, as detailed earlier in the first paragraph of this paper.…”
Section: Bddcs Versus Bcsmentioning
confidence: 86%
“…Today, the science and validity of the BCS are well established, and many Electronic supplementary material The online version of this article (doi:10.1208/s12248-012-9350-9) contains supplementary material, which is available to authorized users. biowaiver extensions have been proposed by the scientific community and some have been approved by regulatory bodies (8)(9)(10)(11). Note: a dichotomy in nomenclature exists between WHO and US documents wherein bioequivalence in WHO terminology refers to a comparative blood level (pharmacokinetic studies).…”
Section: Introductionmentioning
confidence: 99%